Wireless network for computer puzzle online software cloud platform based on CBIR and sustainable computing. (15th November 2021) - Bing, Sun
Wireless network for the computer puzzle online software cloud platform based on the CBIR and sustainable computing is proposed in this paper. In order to improve the ability to resist shortcut attacks, which is generally speaking, encryption algorithms, the higher the number of rounds, the better of the overall performance, because the attack from the crack encryption algorithm. On the other hand, the efficiency of shortcut attack is obviously more than that of exhaustive key search attack high. Hence, we propose two novelty aspects: 1) the CBIR is optimised using the machine learning models to enhance the computational robustness; 2) the WSN and computing models are combined to improve the robustness of the proposed methodology. Our research fins the optimal combination of the wireless systems with the CBIR system that will improve the efficiency. The experimental results have shown that the performance of the model is validated both from accuracy level and robustness level.